Is the Winograd Technique an Effective Method in the Treatment of Ingrown Toenails among the Pediatric Population? - Murat Celal Sözbilen (Galenos Yayinevi, 2021)
Aim:This study aimed to examine the results of the Winograd technique applied in the treatment of ingrown toenail cases, which are frequently encountered in childhood, especially in adolescence. The recurrence, satisfaction, and complication rates in pediatric age groups were evaluated with the surgical matrixectomy application of the Winograd technique, a frequently used one in adult age groups.Materials and Methods:Ingrown toenail cases that had undergone surgical matrixectomy with the Winograd technique between September 2016 and December 2018 were evaluated. Those detected to be stage 2-3 according to the Heifetz classification were operated on. Demographic information was recorded. The cases were divided into three groups as 3-7, 7-12, and ≥12 years as age groups. Such data as recurrence, post-operative infection, osteomyelitis, long term complication and return to regular activity were evaluated. The visual analog scale was used for the satisfaction scale.Results:A total of 162 operated ingrown toenails from 142 children were followed for an average of 21 months (12-38). The mean age of patients was 13.8 years. When the ingrown toenail location was evaluated, the lateral sides (98, 61.2%) of the patients were seen to have been affected more. According to age groups, 65% (105) of the cases were in the group aged 12 years and over. While the frequency of all complications was 8.1% (13), no chronic complications or osteomyelitis were encountered. Recurrence was observed in 3.1% of cases and also early infection (<15 days) was observed in 10 cases, while late infection (<15 day) was observed in 3 cases. According to the visual analog scale scores, 135 (95.0%) cases were found to be satisfactory or very satisfactory.Conclusion:The Winograd technique (surgical matrixectomy) has low recurrence, low complication and high satisfaction rates in all pediatric age groups even with advanced ingrown toenail complaints. Complete excision of the affected matrix with magnification increases the success of the Winograd technique.